2014
DOI: 10.1186/2049-3258-72-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function, body mass index and mortality in a rural elderly Chinese cohort

Abstract: BackgroundPrevious studies have shown that poor cognition and low body mass index were associated with increased mortality. But few studies have investigated the association between cognition and mortality across the entire cognitive spectrum while adjusting for BMI. The objective of this study is to examine the associations between cognitive function, BMI and 7-year mortality in a rural elderly Chinese cohort.MethodsA prospective cohort of 2,000 Chinese age 65 and over from four rural counties in China were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…The MMSE as a general measure of cognitive impairment has been an important predictor of all-cause mortality [28,29]. To date, although few studies have explored the relationship between cognitive impairment and all-cause mortality in China [30][31][32], the existing results support our conclusion that cognitive impairment is independently associated with an increased risk of death in the elderly [13,14]. Moreover, MMSE scores are known to be influenced by education [16].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The MMSE as a general measure of cognitive impairment has been an important predictor of all-cause mortality [28,29]. To date, although few studies have explored the relationship between cognitive impairment and all-cause mortality in China [30][31][32], the existing results support our conclusion that cognitive impairment is independently associated with an increased risk of death in the elderly [13,14]. Moreover, MMSE scores are known to be influenced by education [16].…”
Section: Discussionsupporting
confidence: 64%
“…Although a number of epidemiological studies have reported on a cognitive impairment-mortality relationship [3,7], most of them concerned the association of cognitive impairment and mortality risk of elders in high-income contries [8][9][10][11][12]. In upper-middle income countries such as China, several studies have indicated that baseline cognitive impairment increases the risk of all-cause mortality [13,14]. Earlier studies have found that education is strongly related with cognitive performance [15].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only 2 studies have examined the relationship between baseline cognitive function and mortality in China 5, 6. Gao et al indicated that baseline cognitive function assessed by composite cognitive z‐score predicts future mortality incidence among a rural Chinese cohort aged ≥65 years 6.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 2 studies have examined the relationship between baseline cognitive function and mortality in China 5, 6. Gao et al indicated that baseline cognitive function assessed by composite cognitive z‐score predicts future mortality incidence among a rural Chinese cohort aged ≥65 years 6. An and Liu showed that baseline cognitive impairment measured using the MMSE was inversely associated with longevity, although the population was confined to the oldest Chinese aged ≥80 years 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation